DEVELOPMENT AND INITIAL VALIDATION OF THE STRESS SYMPTOMS SCALE - Dudkina, Aija; Perepjolkina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of this study is to develop and to perform an initial validation of the Latvian and Russian version of the Stress Symptoms Scale. A preliminary version of the scale (k = 65) were administrated to the test development sample as an on-line survey. Additionally participants (N = 272, aged from 19 to 68, M = 37.2, SD = 11.6, 13% male) filled in the Latvian or Russian version of the Perceived Stress Scale-4 (PSS-4), and responded using 10-point scale on two criterion questions about the frequency and intensity of the experienced stress during the last two weeks. Information of their age, gender and education level were collected as well. Based on performed psychometric analysis a final version of the SSS was developed. It consists of 56 items, which can be combined into four scales: 1) Impaired functioning of cognitive processes; 2) Psychological symptoms of stress; 3) Physical symptoms of stress; 4) Emotional symptoms of stress. Based on Exploratory and Confirmatory factor analysis a four-factor solution is preferable. Both versions (LV and RUS) of the scale show excellent internal consistency (Cronbach’s alpha ranged from .92 to .98). Concurrent validity of the SSS was approved by high correlation with criterion-measures. Both versions of the SSS show acceptable to excellent psychometric properties and can be used by psychologists and other mental health professional for the better understanding of individual’s stress reactions and for a reliable evaluation of stress level based on the set of stress symptoms.